Metaphorical representation of the concept love in the ancient greek idylls - Лагутіна, Анна Олегівна (Київський національний університет імені Тараса Шевченка, 2021)
The study presents the results of the peculiarities’ analysis of the metaphorical verbalization of the concept LOVE based on the texts of Ancient Greek Theocritus, Moschus and Bion’s idylls. The study of the peculiarities of the representation of the concept LOVE on the material of Ancient Greek texts is of a particular interest to researchers, as it allows to to model the linguoconceptosphere of the Ancient Greek language speakers. The metaphor in the works of bucolic poets reflects both the general cognition of the feeling of love and the authors’ own cognition. The paper presents a brief overview of the phenomenon of love in Ancient Greece through the prism of Ancient Greek literature, which doubtlessly influenced the works of the idylls’ authors. As a result, the main models of metaphorical transference, which were used to represent the concept LOVE, were singled out and analysed by the source domain. The analysis showed that the most productive of them are: “love is disease”, “love is fire”, “love is deity” and “love is gustatory / physical perception”. Features of the metaphorical representation of the concept LOVE are caused by Greeks’ mythological ideas, the philosophical tradition and established in Ancient Greek culture customs. The concept LOVE in the three studied authors is presented in the same way, which gives us the reason to believe that Moschus and Bion creatively imitated Theocritus.

У дослідженні викладено результати аналізу особливостей метафоричної вербалізації концепту КОХАННЯ на матеріалі текстів давньогрецьких ідилій Феокрита, Мосха і Біона. Дослідження особливостей репрезентації концепту КОХАННЯ на матеріалі давньогрецьких текстів становить особливий інтерес для дослідників, оскільки дозволяє певною мірою змоделювати лінгвоконцептосферу носіїв давньогрецької мови. Метафора у творах буколічних поетів відображає як загальну когніцію почуття кохання, так і власне авторську. У роботі представлено короткий огляд самого феномену кохання в Давній Греції через призму давньогрецької літератури, що беззаперечно вплинуло на творчість авторів ідилій. У результаті були виокремлені та проаналізовані основні моделі метафоричного перенесення, які використовувались для репрезентації концепту КОХАННЯ, за сферою-джерелом. Аналіз показав, що найпродуктивнішими з них є “кохання – хвороба”, “кохання – вогонь”, “кохання – божество” та “кохання – смакові / фізичні відчуття”. Особливості метафоричної репрезентації концепту КОХАННЯ зумовлені міфологічними уявленнями еллінів, філософською традицією та усталеними в давньогрецькій культурі звичаями. Концепт КОХАННЯ у трьох досліджуваних авторів представлений однаково, що дає нам підстави вважати, що Мосх та Біон творчо наслідували Феокрита.
Метафорична репрезентація концепту кохання у давньогрецьких ідиліях
Keywords: концепт КОХАННЯ; метафорична модель; сфера-джерело; Феокрит; Мосх; Біон; давньогрецькі ідилії; Ancient Greek idylls; concept LOVE; metaphorical model; source domain; Theocritus; Moschus; Bion